37th Primary Care Update. Issue 11 (20th November 2017) - David, Felix
Abstract : The 37th Primary Care Update was held at the Royal Society of Medicine in September, informing healthcare professionals on the current UK management of hayfever and inflammatory bowel disease, and the challenge of an ageing population in drug and alcohol detox services. Felix David reports on some of the conference highlights.